2003
DOI: 10.1161/01.str.0000091843.02517.9d
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Stroke Risk

Abstract: Background and Purpose-Whether physical activity reduces stroke risk remains controversial. We used a meta-analysis to examine the overall association between physical activity or cardiorespiratory fitness and stroke incidence or mortality. Methods-We searched MEDLINE from 1966 to 2002 and identified 23 studies (18 cohort and 5 case-control) that met inclusion criteria. We estimated the overall relative risk (RR) of stroke incidence or mortality for highly and moderately active individuals versus individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
356
2
23

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 706 publications
(399 citation statements)
references
References 40 publications
18
356
2
23
Order By: Relevance
“…Furthermore, several epidemiological studies have shown that insufficient physical activity increases mortality rate (Pate et al, 1995;Dumith, 2011;WHO, 2010). RPA has also been associated with reduction of risk factors for the development of cerebral disease (Lee, 2003). every single individual in Australia, the United kingdom and Switzerland ranging from$ 28.40 to $334.40 and indirect costs associated with inactivity ranging from $ 154.70 to$ 418.90 in the United States and Canada (Kohl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several epidemiological studies have shown that insufficient physical activity increases mortality rate (Pate et al, 1995;Dumith, 2011;WHO, 2010). RPA has also been associated with reduction of risk factors for the development of cerebral disease (Lee, 2003). every single individual in Australia, the United kingdom and Switzerland ranging from$ 28.40 to $334.40 and indirect costs associated with inactivity ranging from $ 154.70 to$ 418.90 in the United States and Canada (Kohl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, skipping breakfast increases the likelihood of eating more energy-dense snacks throughout the day. Physical inactivity is another lifestyle behavior associated with an elevated CVD risk (12)(13)(14), not least due to its contribution to weight gain. Since lifestyle is a strong but modifiable risk factor for CVD, it has been the subject of research for many years.…”
mentioning
confidence: 99%
“…Reinforcing the importance of early exercise, a subsequent case-control study assessed the impact of participation in vigorous sports or other physical activities between the ages of 15 and 25 years on later stroke risk [5]. Those who did not exercise had a threefold increased chance of stroke in later life (odds ratio [6]. Combining both types of studies, highly active individuals had a 27% lower risk of stroke or death as compared with persons with lower levels of activity (RR: 0.73; 95% CI: 0.67-0.79), with a similar benefit in those engaging in moderate activity (RR: 0.80; 95% CI: 0.74-0.86).…”
Section: Discussionmentioning
confidence: 99%